Influence of reduced tillage and fertilisation regime on soil quality indicators in an organic potato production system. Issue 2 (3rd April 2018) - Drakopoulos, Dimitrios; Scholberg, Johannes M. S.; Lantinga, Egbert A.
Abstract: The aim of this study was to assess the short-term effects of tillage practice (reduced tillage – RT; standard tillage – ST) and fertilisation regime (solid cattle manure – SCM; lucerne pellets – LP; grass/clover silage – GCS) on soil quality indicators in an organic potato ( Solanum tuberosum L.) production system. Use of RT enhanced the biomass and number of earthworms compared with ST. Concentrations of soil mineral N ( and ) showed similar decreasing patterns over time across both tillage systems during the potato production period. However, soil mineral N was overall higher in the 0–15 cm soil layer for RT and in the 15–30 cm layer for ST. Soil bulk density was higher for RT than ST at 1, 4 and 7 weeks after planting, while a linear reverse correlation was found between soil bulk density and tuber yield. Although both soil temperature and soil moisture content were not found to be greatly affected by tillage practice, net soil N mineralisation was estimated to be 65 kg N ha −1 greater under ST than RT for the potato production period. The application of LP and GCS resulted in higher mid- and end-season soil mineral N concentrations and crop N accumulation at harvest compared to SCM. During initial adaptation to reduced tillage practices in organic potato systems, farmers need to carefully weigh potential conflicts between initial yield reductions and soil conservation goals.